Contribution of Public Speaking to Career Development In The Hospitality Industry - Maharani, Frima; Aulia, Dita; Gigih, Hendri (Journal of Global Hospitality and Tourism Technology, 2024)
Public speaking, or the ability to speak in public, has become an increasingly important skill across various industries, including the hospitality industry. This article aims to review the literature on the contribution of public speaking to career development in the hospitality industry. The importance of public speaking in the hospitality context is underscored by the need for effective communication with various stakeholders, including guests, tourists, customers, and colleagues. Professionals in this industry must be able to convey information clearly, persuasively, and convincingly, both in formal presentations and everyday interactions. Therefore, public speaking skills are crucial for building good relationships with guests, tourists, customers, and colleagues, leading teams effectively, and influencing strategic business decisions. Findings from this literature review reveal that individuals with strong public speaking skills tend to be more successful in securing better career opportunities in the hospitality industry. Those who can speak confidently and convincingly are more likely to be promoted and take on higher managerial responsibilities. Additionally, public speaking skills can open doors for individuals to participate in prestigious promotional activities, seminars, or industry conferences. The discussion in this article highlights the importance of investing in public speaking training and development for professionals in the hospitality industry. Training programs tailored to the context of this industry not only help improve public speaking abilities but also enhance other competencies such as leadership, negotiation, and conflict management. Furthermore, integrating technology into public speaking training can increase accessibility and flexibility for participants. In conclusion, this article finds that public speaking significantly contributes to career development in the hospitality industry. Investment in public speaking skills development is expected to help professionals achieve success and sustainable career growth in an increasingly competitive and dynamic environment.